Obesity and Breast Cancer: Association of Serum Adiponectin, Leptin, and Adiponectin–Leptin Ratio as Risk Biomarkers - Danthala, Madhav; Rajesh, Gogulamudi Ratna; Gundeti, Sadashivudu; Raju, Gottumukkala Suryanarayana; Chandran, Priscilla; Srinivas, Maddali Lakshmi (Indian Journal of Medical and Paediatric Oncology, 2018)
Introduction: Obesity has been associated with the development of breast cancer. The objectives were to study the association of serum adiponectin, serum leptin, and adiponectin–leptin ratio (ALR) in patients with breast cancer and matched controls, and to study their relationship with the various clinicopathological characteristics of breast cancer. Materials and Methods: A prospective, hospital-based case–control study was conducted on 40 patients with a first-confirmed histopathology diagnosis of breast cancer and 40 controls comprising individuals without a history of cancer simultaneously recruited from the health examination clinics during the same study period. Serum adiponectin and leptin concentrations were measured in a single run using commercially available kits (Human ADP/Acrp30 [adiponectin] enzyme-linked immune-sorbent assay [ELISA] kit and Human Leptin ELISA kit, Elabscience Biotechnology Co., Ltd) according to the manufacturer's instructions. Results:: Serum adiponectin levels were reduced significantly in breast cancer patients, in comparison to controls (P = 0.04), while serum leptin levels were increased significantly in breast cancer patients, in comparison to controls (P = 0.03). ALR was significantly lower in breast cancer cases, in comparison to controls (P = 0.05). There was no correlation between receptor status (estrogen receptor, progesterone receptor, Her2/neu), aggressiveness of disease in terms of tumor size, nodal metastases, stage, tumor grade, and serum adiponectin levels, leptin levels, or ALR. Body mass index was negatively correlated with serum adiponectin levels and ALR (r = 0.33, P = 0.03; r = 0.39, P = 0.01, respectively) and positively correlated with serum leptin levels (r = 0.34, P = 0.02). Conclusion: In summary, our results suggest that low serum adiponectin levels, ALR, and high serum leptin levels are associated with breast cancer.
Keywords: Adiponectin; adiponectin–leptin ratio; breast cancer; leptin